The Influence Of Service Quality On Repurchase Decisions With Customer Satisfaction As An Intervening Variable (Case Study Of Coffee Shop Customers In Mataram City) - Rifai, Muhammad; Zulpawati, Zulpawati; Pratiwi, Intan Kusuma (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2025)
This research aims to determine the influence of service quality on repurchase decisions among coffee shop customers in the city of Mataram which is mediated by customer satisfaction, both direct and indirect influences. This type of research is explanatory research which explains the causal relationship between the variables. The data analysis technique used in this research is a quantitative data analysis technique using statistical methods. The data collection technique uses a questionnaire and the statistical method used is Partial Least Square (PLS) using SmartPLS 4 software. From the results of testing the four hypotheses that have been carried out, it can be concluded that service quality has a significant effect on customer satisfaction among coffee shop customers in the city of Mataram. Customer satisfaction has a significant influence on repurchase decisions for coffee shop customers in the city of Mataram, and service quality has a significant influence on repurchase decisions for coffee shop customers in the city of Mataram. Furthermore, service quality has a significant effect on repurchase decisions for coffee shop customers in the city of Mataram, with customer satisfaction as partial mediation.